UPAYA MENINGKATKAN KEMAMPUAN MEMUKUL BOLA KASTI DENGAN PERALATAN YANG DIMODIFIKASIPADA SISWA KELAS IV SEKOLAH DASAR NEGERI 01 GAPURAKECAMATAN WATUKUMPUL KABUPATEN PEMALANG TAHUN PELAJARAN 2014/2015 - Pribadi, Umbar; hendarto, Singgih Hendarto (Jurnal Phederal Penjas, 2014)
The aimof theresearchistoimprove theabilityto hit the ballthroughthe equipmentis modifiedin grade IVState Elementary School01Gapura, District Watukumpul, Pemalangschool year 2014/2015. This study is a Class Action Research (CAR). This study conducted two cycles with each cycle consisting of planning, action, observation, and reflection. Subjects were students of class IV Public Elementary School 01 Gapura, District Watukumpul, Pemalang academic year 2014/2015, the number of 20 students with student details 8 girls and 12 boys. Source of data the study came from the teachers and students. The data collection technique is to onservasi, assessment ability to hit the ball. Validation data using triangulation techniques. Data analysis using descriptive analysis techniques based on qualitative analysis of the percentage. The resultsof this studyfromthe initial conditionsof studentsto the first cycleandcycleII.The results ofthe analysisareobtainedwitha significant increaseoccurred inthe first cycletothe second cycle. On thevalue ofCore CompetenceattitudeI (Spiritual Attitude), konsisibeginningstudentreaches50% or10students, in the first cycleincreased to60% or12students, and the second cycleincreased to80% or16students, andit can be concludedrose to30%or6students. AtCore Competenceattitude scoreII(Social Attitudes), konsisiinitial55% or11students, in the first cycleincreased to75% or15students, and the second cyclerose85% or17students, andcan be summedup 30% or6students.On thevalue ofCore Competenceattitude III (Aspects of Knowledge), konsisi beginning students only50% or10students, in the first cycleincreased to65% or13 students, and the second cycleincreased to 80% or 16 students, and can be summedup 30% or6students. On thevalue of Core Competenceattitude IV (Aspect Skills), konsisi beginning studentsonly 50% or10 students, in the first cycle in creased to65% or 13 students, and the second cycle in creased to 85% or 17 students, and can be summed up 35% or 7 students from 20 student participants. The conclusionsof this research is through the application of the modified equipment canimprove learning outcome sability to hit the ball in the fourth grade students of Elementary School 01 Gapura District Watukumpul Pemalang school year 2014/2015.